Model Tests of the Optimal Location of a New Solution for the Module for Blowing Liquid Steel with an Inert Gas - Merder, T.; Pieprzyca, J.; Wende, R.; Saternus, M.; Warzecha, M.; Socha, L. (Archives of Foundry Engineering, 2026)
This article presents the results of research aimed at determining the optimal location in the bottom of a steel ladle for an module for inert gas injection during the argon process. A physical water model of the ladle was used, constructed according to the principles of similarity, at a linear scale of 1:3.4 relative to the industrial device. This model represents a real object with a capacity of 65 Mg of liquid steel. Two variants of the module's position relative to the base point were adopted for the research, designated at a distance of 0.176 m from the horizontal diameter of the ladle bottom and 0.147 m from the vertical diameter. In variant 1, the longer axis of the module was placed parallel to the horizontal diameter of the ladle bottom, and in variant 2, perpendicular. The research was divided into two stages: quantitative and qualitative. A tracer in form of aqueous KMnO4 solution was used for visualization (qualitative studies), while an aqueous NaCl solution was used to determine the mixing curves (quantitative studies). The minimum mixing time value, determined on the basis of the determined mixing curves, was used as a criterion for assessing the effectiveness of the tested modules in various locations.